Isolation and Antifungal Activity of Caryophyllene from Clove Leaf Oil (Syzygium aromaticum L.) on Mahogany Leaf Composites - Alighiri, Dante (Science and Community Pharmacy Journal, 2022)
Mahogany leaf composites mostly consist of cellulose which is easily weathered due to rotting fungi. One way to overcome this is to use anti-weathering chemicals. Chemical potential as a natural anti-weathering and abundant in Indonesia is caryophyllene compounds as a by-product in the eugenol industry which processes it from clove leaf oil. In this work, isolation and antifungal activity of caryophyllene from clove leaf oil on mahogany leaf composites was evaluated. Based on GC-MS analysis of clove leaf oil is known that eugenol and caryophyllene has yielded 42.83% and 23.87%, respectively. Selective extraction by using sodium hydroxide solution (2,5% NaOH, the ratio of oil to solution is 1:5) and fractional distillation under reduced pressure (Distillate fraction, DF P= -76 cmHg, R=5:1) and continued redistilled are needed to isolate of caryophyllene. Redistilled can improve the purity, then distillate collected while the temperature changed with a purity of 99.10%. Meanwhile, mahogany leaf composite has been successfully synthesized from mahogany leaves by using a polyurethane binder and glass fiber as reinforcement. Minimum inhibitory concentration (MIC) of caryophyllene was determined. The composite was coated with caryophyllene and evaluated for its antifungal activity against Aspergillus fumigatus. Observation using a CCD camera (Charge Couple Device) microscope with a magnification of 50x shows the growth of fungal spores on the composite surface. As a result, A. fumigatus can be inhibited by caryophyllene oil in a 1.2% concentration on mahogany leaf composite